1972
DOI: 10.1007/bf01235635
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Insulin Secretion after Oral Glucose Administration

Abstract: Summary.After sham-feeding of glucose, conscious trained dogs bearing double-barrelled fistulas of the oeso-.phagus or of the stomach do not show any blood sugar mcrease. Nevertheless their Ii%I-lcvels in the peripheral venous blood increased considerably. This increase consists of two peaks of short duration between the 5th and the lOth as well as the 15th and the 25th min. Such IRI-peaks occured also after sham-feeding of tap water, but to a smaller extent. Their temporal order corresponds to the early IRI-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This blood glucose independent early insulin response (EIR) also occurs during ingestion of indigestible dummy meals [1]. The EIR is probably triggered by afferent nervous signals arising from the oropharyngeal cavity [28,29]. Available evidence suggests that efferent vagal projections are involved in the triggering of the EIR: both vagotomy and pharmacological blockade of muscarinic receptors by atropin abolish the EIR [1,4,6].…”
Section: Discussionmentioning
confidence: 99%
“…This blood glucose independent early insulin response (EIR) also occurs during ingestion of indigestible dummy meals [1]. The EIR is probably triggered by afferent nervous signals arising from the oropharyngeal cavity [28,29]. Available evidence suggests that efferent vagal projections are involved in the triggering of the EIR: both vagotomy and pharmacological blockade of muscarinic receptors by atropin abolish the EIR [1,4,6].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that specific tastes or the smell and sight of food can lead to a rapid release of insulin (8,50, 51). In dogs, sham feeding of glucose or plain tap water was able to increase the plasma immunoreactive insulin level (8). Topical anesthesia of the oral mucosa abolished the effect (52).…”
Section: Endocrine Responsesmentioning
confidence: 96%
“…Because oral stimulation can initiate exocrine and endocrine secretions involved in digestion and metabolism (5)(6)(7)(8), attention is currently being given to the nutritional consequences of these physiological secretions. In this paper, we discuss possible nutritional applications of the interrelationships of the chemical senses with eating behavior, digestion, and metabolism.…”
mentioning
confidence: 99%